2003
DOI: 10.14310/horm.2002.1184
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance in pheochromocytoma improves more by surgical rather than by medical treatment

Abstract: Pheochromocytoma, a neuroendocrine tumor, is often associated with hyperglycemia. To investigate the underlying pathogenetic mechanisms, five patients (3 women and 2 men, aged 49+/-2.5, mean+/-SD) with benign adrenal pheochromocytoma were studied with an oral glucose tolerance test (OGTT) and the euglycaemic clamp technique. They were studied preoperatively without taking any medication (stage I), after taking an alpha adrenergic receptor blocking agent (stage II), after taking both an alpha and a beta adrener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 6 publications
(8 reference statements)
0
29
1
1
Order By: Relevance
“…It has been observed that only surgical removal of the lesion can reduce the disorders of glucose metabolism. Therapy with adrenergic α-or β-blocking agents provides only a little therapeutic effect [60]. Patients with pheochromocytoma have less content of both abdominal and subcutaneous fat, and higher HDL--cholesterol concentration, because catecholamines increase lipolysis by activating the adrenergic receptors.…”
Section: Pheochromocytomamentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that only surgical removal of the lesion can reduce the disorders of glucose metabolism. Therapy with adrenergic α-or β-blocking agents provides only a little therapeutic effect [60]. Patients with pheochromocytoma have less content of both abdominal and subcutaneous fat, and higher HDL--cholesterol concentration, because catecholamines increase lipolysis by activating the adrenergic receptors.…”
Section: Pheochromocytomamentioning
confidence: 99%
“…Zaobserwowano, że jedynie chirurgiczne usunięcie zmiany może zmniejszyć nasilenie zaburzeń gospodarki węglowodanowej. Podanie leków blokujących receptory α lub β-adrenergiczne działa w nieznacznym stopniu [60]. Natomiast pacjenci z pheochromocytoma mają mniejszą zawartość brzusznej i podskórnej tkanki tłuszczowej, wyższe stężenie cholesterolu frakcji HDL.…”
Section: Prace Poglądoweunclassified
“…In a small study (n=5) by Diamanti-Kandarakis et al ,14 a slight but statistically significant improvement in glucose homeostasis was seen with the use of adrenergic receptor-blocking agents, and glucose tolerance significantly improved after surgical resection of the tumour. This may be due to the effect of tumour-secreted peptides other than catecholamines 15.…”
Section: Discussionmentioning
confidence: 91%
“…Studies have shown improvement in insulin resistance following adrenalectomy in phrochromocytoma 10 14. Diabetic ketoacidosis is an extremely rare presentation of pheochromocytoma, and the literature is merely reported to few anecdotal case reports 15–19…”
Section: Discussionmentioning
confidence: 99%
“…In general, the regulation of insulin is under dominant inhibitory -adrenoceptor control, principally via the 2-adrenoceptor, with an increase in glucose tolerance on treatment of the phaeochromocytoma. 5 However, as noted above, glycogen stores may have been depleted, and it is conceivable that if adrenaline rather than noradrenaline release was favoured, then -adrenoceptor-mediated effects may have become dominant, even though -adrenoceptors can be shown to increase insulin resistance in vitro. 6 Another possible mechanism for the inappropriately high insulin levels in this patient include direct release from damaged pancreatic tissue given the large area of haemorrhage found at the time of post-mortem examination.…”
Section: Pm 252/06mentioning
confidence: 98%